Sharia Investment: (Investment in Joint Ventures and Associated Entities) and Fixed Assets on Financial Performance in the Jakarta Islamic Index 30 (JII-30) 2021-2024 ndex 30 (Jii-30) Tahun 2021-2024 - Ahmad Muthohar Mujib; Wiwit Mustafidah (SIMFONI: Jurnal Sains dan Sosial Multidisipliner, 2025)
The purpose of this study is to determine whether there is an effect of X1 (amount of investment in joint ventures and associates), X2 (fixed assets) on Y (EPS) in companies listed on the Jakarta Islamic Index 30 (JII-30) for the period 2021-2024, both partially and simultaneously. This study uses a quantitative approach. The data source used is secondary data. The sample used is the quarterly financial reports of manufacturing companies in the food and beverage sub-sector in the Jakarta Islamic Index 30 (JII 30) for the period 2021-2024, totaling 8 companies. The sampling technique used is purposive sampling. The data collection technique used documentation. The data analysis technique used multiple linear regression analysis. The regression results show that 1) X1 (total investment in joint ventures and associates) with a sig. value of 0.784 > 0.05, so there is no significant effect. 2) X2 (fixed assets) with a Sig. value of 0.815 > 0.05, so there is no significant effect. 3) X1 (total investment in joint ventures and associates) and X2 (fixed assets) simultaneously do not have a significant effect on Y (Earnings per Share). The conclusion of this study is that, partially and simultaneously, the variables of sharia investment in joint ventures and associated entities, as well as fixed assets, do not have a significant effect on financial performance as measured by the Earnings per Share (EPS) indicator.